A study on the effectiveness of automated enforcement system camera implementation among road users / Nurul Hafiffah Tumirin - Tumirin, Nurul Hafiffah (Bachelor of Science (Hons) Statistics, 2014)
Automated Enforcement System (AES) is implemented to reduce the number of fatalities on Malaysian roads. Currently, the system is being implemented to reduce cases of speeding and red light running. This study intends to investigate the effectiveness of AES implementation among road users in Malaysia. The data provided from organization (MIROS) where the previous research was conducted by Puan Maslina titled “The public perception and acceptance of implementation of AES”. There were 1075 respondents obtained from Klang Valley and Perak region. The data were analyzed using Statistical Package for Social Science version 18 (SPSS 18.0) and Structural Equation Modeling (SEM) via the Analysis of Moment Structure (AMOS 18) software. The result showing that there was mean difference in perception between before and after of AES implementation among road users. In addition, variable gender moderates the relationship between the perception of being caught and perception of AES implementation. This study can be guideline for the researcher to make some improvement and enhancement for future research in this area